Kohesi Gramatikal Konjungsi Dalam Novel Sang Pemimpin: Sebuah Analisis Wacana - Zetty Karyati; Rahmawati Rahmawati (Peneliti.net, 2020)
The purpose of this study was to obtain information about the grammatical cohesion aspects of conjunctions in the novel Sang Pemimpi. The research method used is qualitative with content analysis techniques. The population of this study was 18 subtitles of the novel Sang Pemimpi, while the study sample consisted of 286 pairs of sentences. The results of the study based on the mechanism of grammatical cohesion markers between pairs of sentences that marked the cohesion level of Sang Pemimpi Novel amounted to 18 titles, 123 paragraphs, and 268 sentence pair data, it can be concluded as follows. The grammatical cohesion aspects of conjunctions used in the novel Sang Pemimpi are additive, causality, temporal, and adversative. The use of grammatical cohesion aspects in the novel Sang Pemimpi is 123 data pairs of sentences from 268 data. The amount of use of grammatical cohesion aspects has the following sequence: (1) additives as much as 85, (2) causality as much as 29 (3) as much as 27 adversative, and (4) temporal as much as 15.